Millets as potential nutri‐cereals: a review of nutrient composition, phytochemical profile and techno‐functionality. (3rd April 2021) - Sharma, Rajan; Sharma, Savita; Dar, B.N.; Singh, Baljit
Summary: Millets are sustainable drought‐resistant crops capable of surviving a wide range of climatic conditions. They are small‐seeded grains rich in proteins, minerals and bioactive compounds inducing several health benefits and provide protection against chronic and degenerative modern lifestyle disorders. Hypoglycaemic profile and bioactive composition are the key elements for the popularity of millets as functional ingredients for the development of novel food products of commercial importance. Despite numerous health benefits and agro‐economic potential, millets have lost their popularity due to coarse nature and are underutilised in developed countries. Food scientists and nutritionists are characterising and valorising millets to enhance their use for food applications. The present article reviews research investigations about nutritional composition (macro‐ and micro‐nutrients), biologically active components (phenolic acid, flavonoids, phytosterols and related antioxidant potential) and techno‐functionality of millets. Pharmacological impact and their utilisation in value‐added products have also been included. Abstract : Millets: Functionality, Bioactivity and Health Benefits.